(untitled) (Marketing Journal, 2024)
In the contemporary globalized economy, regions at various scales, from local municipalities to entire nations, engage in fierce competition to attract scarce resources and talent. Place branding, characterized by the strategic application of branding and marketing techniques, has emerged as a pivotal approach to shaping the economic, social, political, and cultural trajectories of locales. Despite its relatively recent emergence, the scholarly and practical attention towards place branding has steadily intensified over the past two decades. This paper provides an in-depth exploration of place branding strategies, focusing particularly on their role in catalyzing innovation and driving economic growth. Drawing upon theoretical frameworks from marketing, communication, psychology, and sociology, we examine the evolution of place branding theories and the diverse strategies employed in place branding initiatives. Through an analysis of case studies and empirical research, we uncover the nexus between place branding and innovation, highlighting how a compelling place brand can attract talent, stimulate investment, and foster entrepreneurship. Furthermore, we evaluate the economic impacts of effective place branding, including its contribution to tourism revenues, foreign direct investment, and overall GDP growth. However, we also acknowledge the challenges and complexities inherent in place branding efforts, such as stakeholder conflicts and the need for authentic representation. Finally, we propose future research directions to advance our understanding of place branding‘s role in shaping the competitiveness and sustainability of regions in the global economy.